Genetic investigations in childhood deafness. Issue 3 (16th October 2014) - Parker, Michael; Bitner-Glindzicz, Maria
Abstract : Permanent childhood sensorineural hearing loss, is one of the most common birth defects in developed countries. It is important to identify the aetiology of hearing loss for many reasons, as there may be important health surveillance implications particularly with syndromic causes. Non-syndromic sensorineural hearing loss is a highly heterogeneous genetic condition, meaning that it may be caused by any one of numerous genes, with very few phenotypic distinctions between the different genetic types. This has previously presented significant challenges for genetic testing. However, the introduction of new technologies should enable more comprehensive testing in the future, bringing significant benefits to more affected children and their families.